Equity Crowdfunding in Sports Clubs Consumer-Oriented Strategic Marketing - Kościółek, Szczepan (Routledge Research in Sport Business and Management, 2024)
This is the first book to focus on crowdfunding in sport. Crowdfunding is an important new financial instrument that is becoming more popular with sports organisations, and this book examines the research evidence for crowdfunding and considers how it might be successfully implemented. Presenting international cases and data, including from European football, the book explains how crowdfunding campaigns have to be fully integrated with strategic marketing plans and require a solid understanding of the needs and motivations of potential investors, consumers, and fans. The book sets out a theoretical framework for applying strategic marketing in the context of crowdfunding in sports clubs, introduces the key characteristics of the sports crowdfunding market and funders' behaviours in the crowdfunding campaigns of sports clubs, examines the market segments of the campaigns' funders, and presents recommendations for developing marketing-mix programs to target them. This is important reading for any researcher, advanced student, or practitioner with an interest in sport business, sport marketing, sport finance, consumer behaviour in sport, or entrepreneurship, innovation, or technology in sport.